2011
DOI: 10.1186/1751-0147-53-62
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence and nature of cardiac arrhythmias in horses following general anaesthesia and surgery

Abstract: BackgroundThe prevalence and nature of arrhythmias in horses following general anaesthesia and surgery is poorly documented. It has been proposed that horses undergoing emergency surgery for gastrointestinal disorders may be at particular risk of developing arrhythmias. Our primary objective was to determine the prevalence and nature of arrhythmias in horses following anaesthesia in a clinical setting and to establish if there was a difference in the prevalence of arrhythmias between horses with and without ga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 29 publications
(23 reference statements)
0
7
1
1
Order By: Relevance
“…The heart rate may be high before anesthesia in healthy horses because of psychological conditions; therefore, the values of the ECG results (heart rate, systolic pressure, mean pressure, diastolic pressure) may be higher than normal [15]. In our study, systolic pressure before anesthesia was observed to be higher than normal in all groups.…”
Section: Resultscontrasting
confidence: 38%
“…The heart rate may be high before anesthesia in healthy horses because of psychological conditions; therefore, the values of the ECG results (heart rate, systolic pressure, mean pressure, diastolic pressure) may be higher than normal [15]. In our study, systolic pressure before anesthesia was observed to be higher than normal in all groups.…”
Section: Resultscontrasting
confidence: 38%
“…The prevalence of other complications that may occur following surgical management of colic is generally low. These include septic peritonitis , haemoperitoneum , intraluminal haemorrhage , myopathies, gastric rupture , cardiac arrhythmias and derangements in electrolytes , clotting disorders and disseminated intravascular coagulation, pre‐ and post operative renal azotaemia and renal failure . Treatment and preventive strategies for these are detailed elsewhere .…”
Section: Other Post Operative Complications and Future Interventionsmentioning
confidence: 99%
“…Both supraventricular and ventricular premature beats have raised concerns in equine cardiology as potential initiators of atrial fibrillation [2] and fatal ventricular arrhythmias [3]. In recent years, studies have therefore investigated the occurrence of premature beats in healthy horses [48], horses with poor performance [9, 10], and in both clinical [11, 12] and experimental settings [13]. These studies provide valuable information on the prevalence of premature beats, although a comparison of the results is problematic due to different study designs.…”
Section: Introductionmentioning
confidence: 99%